The perfect assassin : a novel - Larsen, Ward (Larsen, Ward. David Slaton novel., 2007)
One perfect shot will change the course of history. Christine Palmer, a young American doctor sailing solo across the Atlantic, makes an incredible discovery - a man narrowly clinging to his life in the frigid waters. But there is much more to this desperate survivor than meets the eye. David Slaton is a Kidon - a highly-trained, highly-precise, and highly-dangerous assassin. The Kidon is both the hunter and the hunted, and he and Christine are in grave danger. Will they win in this race against time?With the precision of a sharpshooter, author Ward Larsen weaves an intricate tale of espionage.